Agama dan Multikulturalisme Masyarakat Bangsa - - Yusdani (Unisia, 2005)
The following article traces several factors cause radical understanding and attitude of religious followers either internal factors or external factors. According to writer, in terms of pluralism, global society and democratization, the notion of religion and the religious attitude that needed by society currently, for Instance multicultural horizon and humanist multicultural. In the context of Indonesia that concerning to human issues and based on the unity in diversity, invite the religion followers in Indonesia to change vision from narrow and normative to historical inclusive and humanist.